1999
DOI: 10.1034/j.1399-0039.1999.530612.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HLA‐A11 serological variant and its characterization by sequencing based typing

Abstract: We have identified an HLA-A11 variant allele, A*1105, segregating in a Caucasoid family. The variant antigen expressed by this allele failed to cross-react with most Caucasoid anti-HLA-A11 antisera tested. Sequencing based typing has been used to characterize this new allele and this showed that it has a novel mutation at a polymorphic position (502) in exon 3. In comparison with A*1101, the mutation (A-->G) results in an amino acid change from positively-charged lysine to negative glutamate and this may expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…A total of 15.8% (17/108) of the samples were homozygous at the sequence level, and the observed heterozygosity was 84.2%. Of all the HLA-A groups studied globally to date, A11 is one of the most common and is highly prevalent in Southeast Asia (26)(27)(28)(29). As in other Asian populations, HLA-A11 allelic variants observed in this study were found to be encoded by the A*1101 and A*1102 alleles (predominantly by A*1101) (17,30,31).…”
Section: Hla-a Allelessupporting
confidence: 53%
“…A total of 15.8% (17/108) of the samples were homozygous at the sequence level, and the observed heterozygosity was 84.2%. Of all the HLA-A groups studied globally to date, A11 is one of the most common and is highly prevalent in Southeast Asia (26)(27)(28)(29). As in other Asian populations, HLA-A11 allelic variants observed in this study were found to be encoded by the A*1101 and A*1102 alleles (predominantly by A*1101) (17,30,31).…”
Section: Hla-a Allelessupporting
confidence: 53%
“…1). Binding to A*1102 was in the same range as to C*0501 and C*1601, and consistently around fourfold higher than to A*1101, a difference correlating with the single substitution—Glu19 in A*1101 and Lys19 in A*1102—that distinguishes them (Morrell et al, 1999). No binding was detected to any of the other 27 HLA-A allotypes tested, which cover the full range of common HLA-A allotypes.…”
Section: Resultsmentioning
confidence: 94%
“…In binding and functional assays, A*1102 was always a better 2DS4 ligand than A*1101. This difference comes from substitution of Glu19 in A*1101 for Lys19 in A*1102 (Morrell et al, 1999). Modeling the 2DS4 interaction with A*11 using the 2DL2–HLA-C*03 structure (Boyington et al, 2000) identified two potential hydrophobic contacts between Lys19 of A*1102 and Phe45 of 2DS4 (∼3.7 Å).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was referred to the DNA Reference Laboratory for investigation by PCR‐SBT. HLA‐A locus PCR‐SBT (2) typed the sample as A*010101 and A*680102 with a single mismatch in exon 2 at nucleotide 275. The A*01 and A*68 alleles were separated by PCR using allele‐specific primers in conjunction with A locus‐specific primers as described earlier (3), and this showed that the mismatch resided in the A*68 allele, at a previously constant position 275 [A→G change].…”
Section: Human Leukocyte Antigen (Hla) Typing Of Three Samples Carrmentioning
confidence: 99%